The Impact of Coastal Livestock Activities on the Health of Dugong (Dugong dugon) Habitats: A One Health Approach in Tropical Regions - Aminurrahman; Amalyadi, Rezki; Karni, Ine; Gifari, Zaid Al; Septian, I Gede Nano (Universitas Madako Tolitoli, 2026)
The Dugong dugon a vulnerable marine herbivore, is closely tied to the health of seagrass ecosystems, which are increasingly threatened by land-based livestock activities in tropical coastal areas. This review explores how nutrient runoff, heavy metal contamination, and microplastics “primarily from livestock farming” contribute to eutrophication, biodiversity loss, and degradation of dugong forage quality. Moreover, the proximity of livestock to marine environments raises risks of zoonotic disease transmission, physiological stress, and mortality in dugongs. Using a One Health framework, this article highlights the ecological and health implications of terrestrial–marine interactions and identifies gaps in research and policy. Recommendations include integrated monitoring, sustainable livestock management, and transdisciplinary collaboration to protect dugong populations and their habitats.